Decision support system for determining chili plant using fuzzy multiple attribute decision making - Sari, Noca Yolanda; Huda, Miftachul; Teh, Kamarul Shukri Mat; Sari, Anggia; Ramli, Ramona; Maseleno, Andino (International Journal of Engineering and Technology, 2018)
Chili is a high value vegetable commodity. Because there are still many people who do not understand the type of superior chili plant. Because all this time the community determines the superior chili plants only by guessing, because of that,Â it was developed a Decision Support System which was used to determine the superior chili plant. Sample (alternative) of this research were 3 types of chili plant, namely cayenne curly chili, large chili. While the criteria used were plant age, plant height, leaf conditions, number of leaves and the results obtained from this study large chili plants are the highest ranked. The method used in determining the superior chili was Simple Additive Weighting (SAW), and the construction of Decision Support System (DSS) to determine superior chili plant using the Delphi 7 application program.